2004
DOI: 10.1086/386278
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gas in the Merging of Massive Black Holes in Galactic Nuclei. I. Black Hole Merging in a Spherical Gas Cloud

Abstract: Using high-resolution SPH numerical simulations, we investigate the effects of gas on the inspiral and merger of a massive black hole binary. This study is motivated by both observational and theoretical work that indicate the presence of large amounts of gas in the central regions of merging galaxies. N-body simulations have shown that the coalescence of a massive black hole binary eventually stalls in a stellar background. However, our simulations suggest that the massive black hole binary will finally merge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
314
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(332 citation statements)
references
References 56 publications
14
314
2
2
Order By: Relevance
“…The population of binary SMBHs depends critically on the efficiency of their coalescence (the so-called Final Parsec Problem; Begelman et al 1980); moreover, whether the binary stalls over the final few parsecs (e.g., Milosavljević & Merritt 2001), coalesces (e.g., Escala et al 2004), or recoils (e.g., Madau & Quataert 2004) has key implications for future gravitational wave detection and the demography of SMBHs.…”
Section: Introductionmentioning
confidence: 99%
“…The population of binary SMBHs depends critically on the efficiency of their coalescence (the so-called Final Parsec Problem; Begelman et al 1980); moreover, whether the binary stalls over the final few parsecs (e.g., Milosavljević & Merritt 2001), coalesces (e.g., Escala et al 2004), or recoils (e.g., Madau & Quataert 2004) has key implications for future gravitational wave detection and the demography of SMBHs.…”
Section: Introductionmentioning
confidence: 99%
“…This process may have an important role in the merging process of SMBHs. Escala et al (2005) studied the effect of the hydrodynamic drag force from dense gas on the evolution of a SMBH binary using numerical simulations. They have shown that after the SMBHs gradually fall into the galactic central dense gas region through dynamical friction, the effect of hydrodynamic drag becomes very large in the central region.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…After the galaxies merge, the SMBHs sink into the center by dynamical friction between the SMBHs and field stars (Ebisuzaki et al 2001;Escala et al 2004Escala et al , 2005. These SMBHs form a SMBH binary and finally merge due to the emission of gravitational waves (Matsubayashi et al 2004;Enoki et al 2004;Escala et al 2004Escala et al , 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our scheme also neglects the role of gaseous-rather than stellar dynamical-processes in driving the evolution of an MBH binary (see, e.g., Escala et al 2004). We will try to address the effect of some these uncertainties on the predicted GWB in x 4.…”
Section: Binary Mergg Er Ratesmentioning
confidence: 99%